Fabrication of rechargeable lithium ion batteries using water-based inkjet printed cathodes. (October 2015) - Gu, Yuan; Wu, Aide; Sohn, Hiesang; Nicoletti, Carley; Iqbal, Zafar; Federici, John F.
Highlights: Water based LiFePO4 ink is studied. Electrodes are made by inkjet printing. Different current collectors are studied. Abstract: Water soluble LiFePO4 inks for lithium ion battery cathodes were prepared and characterized. The pH versus aging time plot shows that stable inks have pH values around 9.13. Inductively Coupled Plasma (ICP) and X-ray Diffraction (XRD) results indicate that impurities are generated as the pH reaches its stable value. Electrical conductivity measurements however suggest that non-electrochemically active impurities lower the electrical conductivity of LiFePO4 . A LiFePO4 particle size change due to different binder adsorption mechanisms on the carbon surface is caused by changes in ion concentration which is determined by the initial pH values. Electrodes are fabricated by inkjet printing using ink prepared with an initial pH of 9.13 on two current collectors (aluminum foil and carbon nanotube paper (CNT paper)). A clear boundary between the aluminum current collector and electrode materials was observed using Scanning Electron Microscopy (SEM), which is possibly caused by the reaction between the alkaline dispersing solvent and the Al foil. XRD results also suggest the existence of impurities like LiAlO2 and AlPO4 after inkjet printing. Despite the uniform morphology of the electrode, electrochemical performance is still poor due to the impurities between the Al current collector and active materials. In contrast, a strong connects between active materials and CNT paper was confirmed by SEM. Battery with CNT paper current collector exhibited better electrochemical performance than Al current collector. This indicates that CNT paper is an alternative to the Al-foil current collector for LiFePO4 aqueous based ink.